Seasonal influence of rainfall and crops on home range expansion by bull elephants - Osborn, Ferrel (Pachyderm, 2003)
’Knowledge of distribution and movement patterns in relation to their environment is essential if elephants are to be effectively managed because crop raiding is spatial and temporal in nature.’ This study attempted to obtain estimates of the home ranges of elephants in Sengwa Wildlife Research Area, to establish seasonal crossing patterns into surrounding communal agricultural lands, and to examine the the concept of wet season range expansion. 7 adult and 3 subadult bulls were radio tracked during a two year period. ’Range sizes and crossing patterns out of the protected area were compared by season.’ Results suggest that the concept of range expansion at the end of the wet season is correlated with the movement of elephants into agricultural lands. Knowing how and when crop raiding elephants move into subsistence agricultural areas that surround many of the protected areas is considered essential to identifying the reason why elephants and people come into conflict.